GAYA KEPEMIMPINAN DEMOKRATIS DAN WORK ENGAGEMENT PADA KARYAWAN DI PT X - Gwyneth Silooy,; Sutarto Wijono, (Journal of Innovation Research and Knowledge, 2025)
This study is motivated by the importance of work engagement in improving employees’ productivity and work quality. One of the factors assumed to be related to work engagement is the use of a democratic leadership style. The purpose of this research is to determine the relationship between democratic leadership style and work engagement among employees of PT X. The research method used was quantitative with a correlational approach. The sample consisted of 141 employees selected using the total sampling technique. The instruments used were the Leadership Democratic Style Scale (LDSS) and the Utrecht Work Engagement Scale (UWES). Data analysis was conducted using the Pearson correlation test with the assistance of Jamovi software. The results showed a positive and significant relationship between democratic leadership style and work engagement. Thus, it can be concluded that the higher the application of the democratic leadership style, the higher the employees’ work engagement. These findings highlight the importance of participatory leadership in enhancing work engagement and productivity in the seafood processing and export sector